Variable base-word positioning in English blends - Aviv Schoenfeld; Evan Gary Cohen; Outi Bat‑El (Lexis: Journal in English Lexicology)
In this paper, we explore the conditions that result in variable base‑word positioning in English blends, where the same base words have variable order, yielding two blends, i.e. blend doublets. In non‑synonymous doublets, such as (egg × prégnant >) éggnant ‘pregnant with egg’ and prégegg ‘egg that counts down pregnancy’, the main factor is that in endocentric blends, the base word that contributes the semantic head is right‑aligned. In synonymous blend doublets, such as plúmpricot ~ ápriplum ‘plum‑apricot hybrid’ (< plum × ápricot), variable base‑word positioning results from at least four factors interacting: (i) segmental faithfulness – maximizing segmental similarity; (ii) Pāṇini’s law – positioning the short base word before the long one; (iii) monosyllabic integrity – keeping the monosyllabic base word in the same syllable; and (iv) syntagmatic faithfulness – matching the linear order of the base words to their order in a would‑be syntactic constituent.